Eddy covariance fluxes of greenhouse gasses observed in a renewed pasture in the southeast of Brazil - Cabral, Osvaldo M.R. (2024)
The recovery of degraded pastures and the increase in their capacity for storing carbon is a key strategy in Brazil's commitment to meeting its Nationally Determined Contribution (NDC) to the international effort to halt global warming. Here we report the fluxes of CO2, N2O and CH4 gasses and their balances, obtained by the eddy covariance method, from a representative pasture area in southeast Brazil. The measurements covered more than five years, starting with the old degraded pasture, covering the renewal process and then the re-establishment of pasture. The latter only received nitrogen fertilization once after the renewal – the common practice. The net ecosystem carbon balance (NECB), which considered the sum of the net ecosystem exchange (NEEpasture) of CO2 and methane (FCH4pasture) without the cattle respiration and enteric fermentation, as well the export/import of carbon by grazing and as feces (stocking rates of 1.8 to 3.3 AU ha−1), was positive in the old pasture (236 ± 104 g CO2 m−2 year−1) representing a source to the atmosphere, but a sink (negative) during the first year of the renewal (-1603 ± 122 g CO2 m−2 year−1) when it was fertilized and the recorded rainfall was normal. In the following two years it was neutral (77 ± 93 and 5 ± 100 g CO2 m−2 year−1), partially a consequence of the lower rainfall received. In the fourth year it was a sink again (-736 ± 131 g CO2 m−2 year−1). On average the cumulative fluxes of CH4 (42 ± 19 g CO2 eq. m−2 year−1) without the animals’ enteric fermentation and N2O (20 ± 10 g CO2 eq. m−2 year−1) were small and positive, being offset by the net carbon gain. The NECB for this site covering the period of measurements was an overall source of 671 ± 254 g CO2 m−2.